Drug tolerance/intolerance in domestic dog (Canis lupus familiaris) with MDR1 gene defect - Zdańkowski, Sebastian; Gruszczyńska, Joanna; Fiszdon, Katarzyna; Siewruk, Katarzyna; Grzegrzółka, Beata; Świderek, Wiesław (Folia Pomeranae Universitatis Technologiae Stetinensis Agricultura, Alimentaria, Piscaria et Zootechnica, 2017)
Ivermectin is a drug used to fight endo- and exoparasites in animals at regular base in veterinary practice. Basically this substance is safe for mammals. The mechanism of its action is based on dysfunction of nerve impulses conduction. P-glycoprotein is a membrane transport protein present in endothelial cells of lungs, kidneys, liver and pancreas. It prevents toxin penetration into the brain neurons and many other organs outside central nervous system including barriers: blood–testis, blood–placenta, blood–urine. This protein is coded by Multi Drug Resistance gene 1 (MDR1 gene) and is located in membranes of blood-brain barrier cells. When a mutation in MDR1 gene appears the protein isn’t able to function properly. In that case ivermectin goes to canine central nervous system cells and induces neurotoxic clinical signs, that is why early diagnostic is very important especially to prevent poisoning. The reasons and effects of the mutation as well as elements of molecular diagnostic that allows to identify the mutation were describe in this manuscript. Moreover, medicines that can induce neurotoxic signs in dogs with mutation in MDR1 gene were listed. Iwermektyna to lek stosowany na szeroką skalę w zwalczaniu pasożytów wewnętrznych i zewnętrznych zwierząt. Jest to związek bezpieczny dla ssaków. Mechanizm jego działania opiera się na zaburzeniu przewodzenia impulsów nerwowych. Glikoproteina P jest błonowym białkiem transportowym obecnym w komórkach endotelialnych wielu narządów, takich jak płuca, nerki, wątroba, trzustka itd. Hamuje ono przedostawanie się toksyn do komórek nerwowych mózgu i ich penetrację. Pełni też swoją funkcję wobec innych narządów, poza układem nerwowym; są to np. bariery: krew–jądro, krew–łożysko, krew–mocz. Białko to jest kodowane przez gen MDR1 (ang. Multidrug Resistance Gene) i znajduje się w błonach komórkowych bariery krew–mozg. W przypadku wystąpienia mutacji genu MDR1 białko powstałe na podstawie zmienionej informacji genetycznej nie jest zdolne do pełnienia swoich funkcji. W takim ...